Physiological Effects and Prescription of Exercise in Patients with Peripheral Artery Disease - Arnengsih Nazir (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Peripheral artery disease (PAD) is a disease with atherosclerotic process in blood vessels which results in impairment of blood flow to the lower limbs. The prevalence escalates with advancing age and resulting in typical symptoms of intermittent claudication, ischemic pain at rest, non-healingwound, and atypical symptoms associated with PAD. These symptoms can lead to impaired walking, activity restrictions, and low quality of life. Regular exercise has been known as an effective intervention to reduce symptoms and improve exercise performance.Methods: Literature published from 2011-2021 was searched using the PubMed and Google Scholar as the search engine. The keywords used were exercise, physiological effect, recommendation, peripheral artery disease, and intermittent claudication.Results: Forty-four literature matched with the topic and 1 1 were used to explain sub-topics.Conclusion: The physiological effects of regular exercise include increased of oxygen extraction from blood vessels and muscle enzyme activity, as well as decreased of inflammatory mediators associated with endothelial damage. The recommended form of exercise for PAD is walking both under supervisionand without supervision at home and community. Prescription of aerobic exercise vary based on intensity targeted. Another forms of exercise recommended for PAD patients are resistance and flexibility exercises.Keywords: exercise, peripheral artery disease, physiological ef fects, supervised-exercise.